Revisiting Vitamin and Trace Mineral Nutrition in Atlantic Salmon Farming With Emphasis on Fish Health - Antony J. P. Philip; Trond M. Kortner; Pauline Wischhusen; Kristin Hamre; Åshild Krogdahl; Kaja H. Skjærven; Guro Løkka; Gerd M. Berge; Marit Espe; Nini H. Sissener (Reviews in Aquaculture, 2025)
Atlantic salmon farming is faced with numerous environmental and production‐related challenges affecting fish health and welfare, globally and in Norway. An animal's requirement for a nutrient is the sum of the required supply of available nutrients for maintenance, growth, reproduction, health, and disease resistance. Available literature on micronutrient requirements (vitamins and trace minerals) was reviewed to identify knowledge gaps with a focus on health and disease resistance, potential life stage and production system‐specific differences. Atlantic salmon's minimum requirement estimate for vitamin A was not available, while data on vitamins C, D, E, and K differ greatly between studies due to factors such as feed composition and rearing conditions (stress). Knowledge of the requirements of B‐vitamins is also scarce. Choline requirement in Atlantic salmon was recently estimated and is strongly affected by dietary lipid consumption. Dietary trace mineral needs differed with diet composition and between freshwater and seawater, largely influenced by differences in availability. Dietary trace mineral availability in practical feeds is a concern, especially for zinc and selenium being the most limiting in plant ingredient‐based feeds and supplementation restricted by maximum limits that are too low for optimal fish health. Hence, there is a need for renewed focus on how vitamin and trace mineral recommendations in Atlantic salmon feeds are assessed (research) and managed (regulation). Recommendations will have to be revised considering specific life stages, environmental and physiological changes, health status, and evolving production methods in commercial Atlantic salmon farming.